The Role of E-Satisfaction in Mediating the Relationship of E-Service Quality on E-Loyalty: (A Study on Bukalapak E-Commerce Application Users in Denpasar) (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The advancement of information technology has transformed consumption patterns, including shopping activities that have increasingly shifted to digital platforms or e-commerce. Bukalapak, as one of the early players in this industry, is currently facing challenges in the form of declining market share and user complaints related to digital service quality (e-service quality). This research aims to analyze the effect of electronic service quality on consumer loyalty (e-loyalty), with electronic satisfaction (e-satisfaction) as a mediating variable among Bukalapak users in Denpasar City. The sampling technique employed a non-probability sampling method with a purposive sampling approach, and the number of samples was determined based on the number of indicators used. The research findings indicate that electronic service quality has a positive and significant effect on both user satisfaction and user loyalty. Electronic satisfaction is also proven to significantly affect user loyalty and serves as a partial mediator in the relationship between service quality and loyalty. These findings affirm that improving the quality of digital services can enhance customer satisfaction and ultimately build loyalty toward the Bukalapak platform